Bahder Djohan’s Struggle: The Doctor’s Contribution to National Independence, Language, Emancipation, Social Affairs, and Education - Nelmawarni; Fikri Surya Pratama; Zainal Arif (Paramita: Historical Studies Journal, 2025)
Abstract: Within the domain of postcolonial nation-building and educational reform in countries of the Global South, the role of local intellectuals is frequently marginalised in international discourse. This article examines the figure of Bahder Djohan (1902–1981), an important yet relatively obscure figure in the context of modern Indonesian history. During his tenure as Minister of Education and Culture in the early days of independence, Djohan proposed a vision of education that integrated Minangkabau traditions, Islamic values, and the legacy of colonial education. The approach adopted by the aforementioned individual was such that education was regarded as a means of fostering moral character and facilitating social mobility, without the concomitant abandonment of local cultural roots. Utilising a qualitative approach, this article employs character study and historiography methods to provide a reconstruction of Djohan's biography. Furthermore, it conducts an analysis of his contributions to youth activism, women's emancipation, and post-independence institutional reform. Djohan eschewed imported ideological frameworks, instead developing his thinking through practical involvement in health development, gender equality, and national education. Djohan demonstrated equality of values with global figures such as Gandhi, Freire, and Tagore, especially in his struggle against colonial discrimination and his advocacy for social justice and cultural preservation. Nevertheless, his legacy remains conspicuously absent from both national curricula and international studies. The present article situates Djohan within the global discourse on postcolonial reform, thereby emphasising the importance of recognising local actors as key agents of change and agents of universal values in the history of global ideas. Abstrak: Dalam konteks pembangunan bangsa pasca kolonial dan reformasi pendidikan di negara-negara Global Selatan, peran intelektual lokal kerap terpinggirkan dalam wacana internasional. Artikel ini mengangkat sosok Bahder Djohan (1902–1981), tokoh penting namun kurang dikenal dalam sejarah Indonesia modern. Sebagai Menteri Pendidikan dan Kebudayaan pada masa awal kemerdekaan, Djohan menawarkan visi pendidikan yang menyatukan tradisi Minangkabau, nilai-nilai Islam, dan warisan pendidikan kolonial. Pendekatannya menjadikan pendidikan sebagai sarana pembentukan karakter moral dan mobilitas sosial, tanpa melepaskan akar budaya lokal. Melalui pendekatan kualitatif dengan metode studi karakter dan historiografi, artikel ini merekonstruksi biografi Djohan serta menganalisis kontribusinya dalam aktivisme pemuda, emansipasi perempuan, dan reformasi kelembagaan pascakemerdekaan. Djohan menolak kerangka ideologis impor, dan justru membangun pemikirannya melalui keterlibatan praktis dalam pengembangan kesehatan, kesetaraan gender, dan pendidikan nasional. Djohan menunjukkan kesetaraan nilai dengan tokoh global seperti Gandhi, Freire, dan Tagore, terutama dalam perjuangannya melawan diskriminasi kolonial dan advokasinya terhadap keadilan sosial serta pelestarian budaya. Namun, warisannya masih absen dalam kurikulum nasional dan kajian internasional. Dengan menempatkan Djohan dalam diskursus global tentang reformasi pascakolonial, artikel ini menegaskan pentingnya merekognisi aktor lokal sebagai pelaku utama perubahan dan agen nilai universal dalam sejarah ide-ide global.